2021
DOI: 10.3390/ijerph18020651
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors Affecting the Severity of Metro Escalator Injuries in the Guangzhou Metro, China

Abstract: Urban rail transit has become one of the indispensable modes of public transportation in large cities. Escalators are ubiquitous in metro stations, as passengers typically use escalators when entering or leaving a metro station. Thus, escalators have become an accident-prone location. To develop suitable prevention strategies, it is necessary to understand the risk factors that affect the severity of escalator accidents. This study analyzed 967 escalator passenger accidents that occurred in the Guangzhou Metro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Considering the complexity of consequences caused by multiple passengers’ unsafe behaviors, non-linear models have attracted more attention to measure the interactions between unsafe behaviors and severity of consequences in recent years. 15 , 19 , 20 For instance, Xie et al used ISM-DEMATEL to explore the relationship among escalators, passengers and environment in subway station. 18 In 2020, Wang et al analyzed 40 typical metro operation accidents, which were divided into four levels according to the severity of consequence including high, medium, low and insurance accidents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the complexity of consequences caused by multiple passengers’ unsafe behaviors, non-linear models have attracted more attention to measure the interactions between unsafe behaviors and severity of consequences in recent years. 15 , 19 , 20 For instance, Xie et al used ISM-DEMATEL to explore the relationship among escalators, passengers and environment in subway station. 18 In 2020, Wang et al analyzed 40 typical metro operation accidents, which were divided into four levels according to the severity of consequence including high, medium, low and insurance accidents.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that standing instability was the most likely factor to induce accidents, and among the types of injuries caused to passengers, head and neck injuries were more serious. 19 Although these non-linear models have important superiority in revealing the relevance of passengers' unsafe behaviors and accident consequences, 4,15,19,20 a low prediction of accident risk may appear, as they did not consider the effect of different behaviors on the accident type and severity of metro operation. Moreover, due to the uncertainty of behavior occurrence and its consequence, behavioral risk is not a certain value but obeys a certain distribution in statistical significance, which is always omitted.…”
Section: Introductionmentioning
confidence: 99%